(3GdOQQ aj ENJUGQ GdeZGRi hGdSjQs - (3jhSa Hf YHO Gddg Hf YHO GdHQ GdfeQj GdbQWHj GdeGdcj, GHf YHO GdHQ , CHh YeQ , J (B463 (3g` s
(3ChdgG (B:s
(3Chdg HYO GdOjHGLI (B: (3gPG cJGH ENJUQJ ajg PcQ eHYK GdfHi Udi Gddg Ydjg hSde hEHJOGA fHhjJg s
(3BNQgG (B:s
(3acTa Gddg QHg GdcQHI ef Cgd GdQOI hbGe Hg GdOjf , hGdMeO ddg QH GdYGdejf s
(3GNJUQ ef SQI GHf ESMGb QhGjI GHf gTGe hef cJGH ehSi eQJVi GdMSjfi GdRHjOi UGMH JGL GdYQhSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B240 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B315s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B59 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
Keywords: (3GdJGQjNs